Development Strategy of Onaloan Danau Rusa as a Tourism Destination - Muhd. Arief Al Husaini; Wahyu Hidasyat (Institute of Computer Science (IOCS), 2021)
Kampar regency knows the tourism industry is an important thing as an economic generator, it's shown in the middle scale development document. Onaloan Danau Rusa is one of potential tourism in XIII Kota Kampar district. The problem at that time is an unordered layout of the area, it make the area does not grow up. The research aim is to produce the Onaloan Danau Rusa development model. This research is using the descriptive qualitative method with synchronic reading data. Collecting data are doing observation, in-depth interviews, and literature review. The result is a development tourism area model with architecture engineering that visualization is easy to understand. The design approach is sustainability development with the environmental graphic design concept.